Smart Medicine Box With Mobile Application - Ahmad, Nur Azliza; Asmawi, Norizzmier; Zairul, Arsyad; Amran, Ammar (Multidisciplinary Applied Research and Innovation, 2023)
A lot of medical issue is happen due to the facts that a lot of patients need to deal with sorting a large amount of medicine everyday. This is the main reason of the project Smart Medicine Box (SMB). This protoype is used to help the patients in the area of remembering and helping people to take medicine. Main focus of SMB is for the patients who need medical attentions more than the other. SMB is programmable through mobile application that enable the doctor to deternmined the schedule for the patients to take the medicine. The SMB contains twenty-one partition that have twenty-one LED for the user can set the schedule based on week. SMB will remind the patient by sending the notification through the mobile application and also the LED will lights up when the time for eat the medicine have come.